Branding & Employer Branding Citra Perusahaan untuk Menarik dan Mempertahankan Talenta - Ade Satria Purnama; Haryati Pertiwi; Singgih Puji Raharjo; Arfiani Yulianti (Jurnal Ekonomi dan Bisnis Digital, 2025)
In an era marked by globalization and increasingly complex business competition, organizations are required to build a strong reputation not only among consumers but also among employees and prospective talents. Employer branding emerges as a strategic approach to shaping a positive organizational image as an attractive workplace, aiming to attract and retain high-quality human resources. This approach applies not only to private institutions but also to public sector organizations. In the governmental context, employer branding is utilized to strengthen public service quality, foster professionalism, and secure top talents committed to serving the nation. This study examines the relationship between corporate branding and employer branding within human resource management, while exploring their implications for organizational competitiveness. Using a literature review method grounded in theories of branding, employer branding, and talent management, the findings reveal that employer branding in both sectors plays a crucial role in enhancing talent attraction, reducing turnover rates, and building employee loyalty.